Social Studies Content Knowledge Interventions for Students With Emotional and Behavioral Disorders: A Meta-Analysis. Issue 1 (January 2021) - Garwood, Justin D.; McKenna, John W.; Roberts, Garrett J.; Ciullo, Stephen; Shin, Mikyung
The importance of social studies and civics education is increasing, as evidenced by the growing number of states requiring coursework in this area for graduation and its growing presence in school accountability frameworks. Social studies instruction is critical for all students so that they may understand their roles, rights, and responsibilities as citizens and how their actions can influence their communities. Students who exhibit antisocial behaviors, such as those with emotional and behavioral disorders (EBD), may especially benefit from social studies and civics education as it promotes college and career readiness and provides opportunities to engage in social problem solving and perspective taking. The purpose of this study was to systematically review the social studies and civics intervention research for students with EBD. We sought to describe and evaluate the extant literature, identify promising practices, and suggest areas for future research. A total of 17 intervention studies were identified. Overall, 10 out of the 17 studies met What Works Clearinghouse Design Standards with or without reservations. Eight of the 10 studies were eligible for effect size calculation, resulting in an overall large effect ( g = 0.83). Study limitations, implications for school practice, and directions for research are discussed.